2015
DOI: 10.1016/j.ijsolstr.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Graphene resting on substrate: Closed form solutions for the perfect bonding and the delamination case

Abstract: a b s t r a c tWe study closed form solutions for the perfect bonding and the delamination case for a monolayer graphene sheet resting on an elastic foundation. The theoretical framework we adopt is restricted to the materially and geometrically linear case. Graphene is modeled as a hexagonal 2-lattice, while the substrate is assumed to behave in an isotropic linearly elastic manner. Initially, we ignore out-of-surface motions and study the case of biaxial tension/compression and simple shear. We find the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In any case, the present results show that even for simply supported graphenes lateral wrinkling initiates at a far smaller strain than the tensile fracture strain. Such modes of failure have been studied theoretically in recent works 28,29 and as the experiments confirm here are omnipresent 30 when graphenes of micron dimensions are loaded in tension. In fact, this type of failure modes is quite common for supported thin films when the underlying substrate is relative stiff (here the modulus of the substrate is ∼3 GPa).…”
Section: Tensionsupporting
confidence: 57%
“…In any case, the present results show that even for simply supported graphenes lateral wrinkling initiates at a far smaller strain than the tensile fracture strain. Such modes of failure have been studied theoretically in recent works 28,29 and as the experiments confirm here are omnipresent 30 when graphenes of micron dimensions are loaded in tension. In fact, this type of failure modes is quite common for supported thin films when the underlying substrate is relative stiff (here the modulus of the substrate is ∼3 GPa).…”
Section: Tensionsupporting
confidence: 57%
“…Graphene on a substrate has been modelled analytically as a hexagonal 2-lattice and studied using continuum mechanics 15,16 . Other effects such as the sequential period-doubling bifurcations for graphene bonded to a PDMS substrate were also studied numerically 17 .…”
mentioning
confidence: 99%
“…Dependence on the shift vector, p , at the continuum level, results from well established theories of multilattices [2128]. If we confine ourselves to weak transformation neighbor- hoods [28] and assume validity of the CauchyBorn rule [29] graphene’s elastic energy for the geometrically and materially linear case has the form [4, 6]…”
Section: Mathematical Preliminariesmentioning
confidence: 99%
“…where e ij f = 1 2 ( u i , j f + u j , i f ) is the in-surface strain measure of the film, u f is the displacement of the film, b f is film’s curvature, while p is graphene’s shift vector. Tensors C i , i = 1 , , 6 are related with the material parameters of the problem at hand (see the work by Sfyris et al [4, 6]) which are found to have nine material parameters denoted by c i , i = 1 , , 9 and will be discussed in Section 5. Quantities related with residual/internal strains are denoted by the superscript “0”.…”
Section: Mathematical Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation